2014
DOI: 10.1002/hep.27218
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of far upstream element (FUSE) binding protein (FBP)-interacting repressor (FIR) supports growth of hepatocellular carcinoma

Abstract: The far upstream element binding protein (FBP) and the FBP-interacting repressor (FIR) represent molecular tools for transcriptional fine tuning of target genes. Strong overexpression of FBP in human hepatocellular carcinoma (HCC) supports tumor growth and correlates with poor patient prognosis. However, the role of the transcriptional repressor FIR in hepatocarcinogenesis remains poorly delineated. We show that overexpression of FIR correlates with tumor dedifferentiation and tumor cell proliferation in about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 27 publications
(89 reference statements)
2
46
0
Order By: Relevance
“…In addition, BLM-induced DNA damage alters FIR splicing, which contributes to the transcriptional upregulation of c-myc via dominant negative effect on endogenous FIR [12, 13]. c-Myc accelerates the cell cycle by suppressing p27Kip1 expression, eventually leading to the accumulation of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, BLM-induced DNA damage alters FIR splicing, which contributes to the transcriptional upregulation of c-myc via dominant negative effect on endogenous FIR [12, 13]. c-Myc accelerates the cell cycle by suppressing p27Kip1 expression, eventually leading to the accumulation of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Markedly, a splice variant of FIR that lacks exon 2 in the transcriptional repression domain (FIRΔexon2) elevates c-Myc protein expression in vitro [11]. FIRΔexon2 mRNA is frequently upregulated in human colorectal cancers [12] as well as hepatocellular carcinoma [13], where it stimulates tumor growth by preventing FIR from suppressing c-myc [13]. FIRΔexon2 functions as a dominant negative regulator of FIR; therefore it reduces FIR function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that genetic variants at 8q24 are associated with the risk of many kinds of tumors including hepatocellular carcinoma [17][18][19]. Interestingly, the lncRNA CARLo-5 is known to be located in the 8q24.21 gene desert [13].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the far-upstream element (FUSE)-binding protein-interacting repressor (FIR), splicing variant of PUF60 lacking exon5, have been reported to be overexpressed in various malignant tumors, such as colorectal cancers [2, 3], hepatocellular carcinomas [4, 5], T-cell acute lymphoblastic leukemia [6],and non-small cell lung cancer [7]. Therefore, it is natural that anti-FIR (PUF60) antibodies could be detected in the sera of cancer patients as well as in dermatomyositis and Sjogren's syndrome.…”
Section: Introductionmentioning
confidence: 99%